Penerapan Akad Ijarah Pada Produk Pembiayaan Pengurusan Porsi Haji Di KSPPS Kopena Pekalongan Ditinjau Dari Fatwa DSN-MUI - Danis Amwalul Fikki (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2019)
Purpose- This study discusses the application of the Ijarah Agreement on Financing Products for the Management of Hajj Portions at KSPPS Kopena Pekalongan Judging from the DSN-MUI Fatwa. Methods- This research is a type of field research with a type of qualitative approach. The data used in this study are primary data obtained from interviews and secondary data obtained from research at KSPPS Kopena Pekalongan. Data were analyzed descriptively, namely data collected in the form of words, images and not numbers. The method of data collection by interviews, documents, and observations. Findings- The results of the study show that financing using the ijarah contract has followed the rules of the MUI DSN Fatwa. It can be stated that KSPPS Kopena Pekalongan has implemented the DSN-MUI Fatwa in each of its products and the Sharia Supervisory Board has always exercised strict control over the application of fatwas at the KSPPS Kopena Pekalongan Implications/limitations - This study is a case study and is only carried out in one agency so that future studies can expand the study area to increase generalization.